A social cognitive model of entrepreneurial intentions in university students - Lanero, Ana; Vázquez, José-Luis; Muñoz-Adánez, Alfredo (Anales de Psicología / Annals of Psychology, 2014)
This work analyzes the limitations of previous literature on entrepreneurial intentions of university students and set a model of entrepreneurship career choice based on the Social Cognitive Career Theory (SCCT) developed by Lent, Brown and Hackett (1994, 2000). Particularly, the study hypothesizes a sequential direct path between entrepreneurial vocational interests, intentions and nascent behaviors, which in turn would be triggered and reinforced by the beliefs of self-efficacy and outcome expectations attributed to business start-up. To test the hypotheses of the model, an empirical study carried out with 400 university students within different knowledge areas is described. The results obtained, using the PLS (Partial Least Squared) technique confirm a positive direct link between entrepreneurial interests, intentions and behaviors, while perceived entrepreneurial self-efficacy predicts that goal sequence. Otherwise, outcome expectations only impacts on vocational interest in business start-up. These findings have important implications for the design of entrepreneurship support programs in university environments.